Effect of garlic (Allium sativum) extract on the control of the three main infectious agents of bovine mastitis - Chumbe Valqui, Wuilder Pablo (2022)
The objective of this study was to evaluate the antibacterial effect of garlic extract (Allium sativum) in the control of the three main agents of bovine mastitis, Escherichia coli, Staphylococcus aureus and Streptococcus agalactiae. The concentrations used were 0%, 20%, 40% and 60% garlic extract (EA) in distilled water. Milk with signs of mastitis was used, the supernatant of the sample was eliminated to obtain the bacteria concentrate and then sowed in the culture media: Mac Konkey, Salted Mannitol and Blood Agar; it was incubated for 24 hours at 37°C. Subsequently, it was seeded for the differential of Escherichia coli, Staphylococcus aureus and Streptococcus agalactiae. The most efficient antibacterial effect for Escherichia coli and Streptococcus agalactiae was the 60% concentration, while for Staphylococcus aureus it was 40%. As well as the EA with the concentrations of 40 and 60% proved to be effective in the in vitro control against bovine mastitis precursors.